A non-compensatory time analysis of material deprivation in the EU - Ciacci, Andrea; Traversa, Susanna (Revista de Estudios Andaluces, 2021)
The financial and economic crisis that hit Europe since 2009 has highlighted the need to measure more effectively the impact that certain exogenous shocks can have in the social field. In order to fill this gap and to provide a statistical tool useful to measure phenomena evolving over time, we perform a non-compensatory time analysis of material deprivation in Europe by using the quantitative method known as Adjusted Mazziotta and Pareto Index (AMPI). Material deprivation is a proxy to identify the most suffering groups of people in a specific environment. We consider the material deprivation as the sum of economic stress and forced lack of durable goods. Using Eurostat EU-SILC data, we aim at determining which countries have suffered the most material deprivation and identifying clusters of deprivation. We also determine how material deprivation is evolved over time, from 2005 to 2019. Subsequently, through Influence Analysis, the robustness of the index obtained is evaluated. Our results show that the material deprivation gap between Eastern and Mediterranean countries and all the remaining countries, which already existed before the economic crisis, seems to have widened in the years up to 2015.